Lung cancer risk by geologic coal deposits: A case–control study of female never‐smokers from Xuanwei and Fuyuan, China. Issue 12 (15th January 2019) - Wong, Jason Y.Y.; Downward, George S.; Hu, Wei; Portengen, Lützen; Seow, Wei Jie; Silverman, Debra T.; Bassig, Bryan A.; Zhang, Jinming; Xu, Jun; Ji, Bu‐Tian; Li, Jihua; He, Jun; et al.
Abstract : Coal types vary around the world because of geochemical differences in their source deposits; however, the influence of coal emissions from different deposits on human health remains unexplored. To address this issue, we conducted the first study of the relationship between coal use from various deposits and lung cancer risk in Xuanwei and Fuyuan, counties in China where lung cancer rates are among the highest in the world among female never‐smokers due to use of bituminous ("smoky") coal for heating and cooking. We conducted a population‐based case–control study of 1031 lung cancer cases and 493 controls among never‐smoking women in Xuanwei and Fuyuan. Logistic regression models were used to estimate associations between coal use from various deposits across the lifecourse and lung cancer risk. There was substantial heterogeneity in risks by coal deposit ( p = 7.8E‐05). Compared to non‐smoky coal users, risks by smoky coal deposit ranged from OR = 7.49 (95% CI: 3.43–16.38) to OR = 33.40 (95% CI: 13.07–85.34). Further, women born into homes that used smoky coal and subsequently changed to non‐smoky coal had a higher risk (OR = 10.83 (95% CI: 4.61–25.46)) than women born into homes that used non‐smoky coal and changed to smoky coal (OR = 4.74 (95% CI: 2.03–11.04, p difference = 0.04)). Our study demonstrates that various sources of coal have considerably different impact on lung cancer in this population and suggests that early‐life exposure to carcinogenic emissions may exert substantial influence on health risks later in life. These factors should be considered when evaluating the health risks posed by exposure to coal combustion emissions. Abstract : What's new? Indoor coal combustion emissions have been designated as Group 1 carcinogens. However, the influence of emissions from coal originating from different geological deposits remains unexplored. Lung cancer rates in the rural counties of Xuanwei and Fuyuan in China are among the highest in the world due to indoor combustion of bituminous ("smoky") coal. Using detailed lifecourse data on household fuel sources, the authors conducted the first study to show that lung cancer risk varies by the geological deposit of household coal. Notably, childhood exposure to smoky coal may have an important impact on lung cancer risk later in life.